2021
DOI: 10.2147/opth.s328493
|View full text |Cite
|
Sign up to set email alerts
|

A Genotype–Phenotype Analysis of the Bardet–Biedl Syndrome in Puerto Rico

Abstract: Background: Bardet-Biedl syndrome is a complex heterogeneous ciliopathy caused by genetic mutations. Although establishing genotype-phenotype correlations has been challenging, some regional variations have been previously reported. Due to its relative geographic isolation, Puerto Rico has a greater prevalence of Bardet-Biedl syndrome than do other regions. We sought to characterize the most frequent genotypic variations in a local cohort of Bardet-Biedl syndrome patients and report any genotypic-phenotypic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
3
4
Order By: Relevance
“…Homozygous variants were noted in 10 patients (50.00%) and 10 (50.00%) compound heterozygous variants were noted in our series. Unlike a report from the United States ( Guardiola et al, 2021 ), which reported hot spot variants in BBS1 and BBS7 , at least 11 variants of BBS7 were reported in this series. The most common variant was the c.1002delT (p. Asn335Ilefs*47) variant, which was found in 7 patients (36.84%) from 5 families, including 2 homozygotes.…”
Section: Resultscontrasting
confidence: 98%
See 4 more Smart Citations
“…Homozygous variants were noted in 10 patients (50.00%) and 10 (50.00%) compound heterozygous variants were noted in our series. Unlike a report from the United States ( Guardiola et al, 2021 ), which reported hot spot variants in BBS1 and BBS7 , at least 11 variants of BBS7 were reported in this series. The most common variant was the c.1002delT (p. Asn335Ilefs*47) variant, which was found in 7 patients (36.84%) from 5 families, including 2 homozygotes.…”
Section: Resultscontrasting
confidence: 98%
“…Except for one case without detailed data of variant, 19 BBS2 patients from 12 families were reported ( Xing et al, 2014 ; Chen et al, 2017 ; Li et al, 2017 ; Ding et al, 2018 ; Dan et al, 2020 ; Huang et al, 2021 ; Meng et al, 2021 ; Tang et al, 2022 ; Tao et al, 2022 ; Wei et al, 2022 ), including 12 (63.16%) compound heterozygous variants and 7 (36.84%) homozygous variants. Unlike report from the United States ( Guardiola et al, 2021 ), which reported hot spot variants in BBS1 and BBS7 , a total of 15 variants were reported in our series. The most common was the c.534+1G>T splicing variant in 9 patients (47.37%) from 5 families, including 2 homozygotes.…”
Section: Resultscontrasting
confidence: 95%
See 3 more Smart Citations